Modification of the Magnetic and Electronic Properties of the Graphene‐Ni(111) Interface via Halogens Intercalation. Issue 1 (23rd November 2021) - Zhou, Yong; Ovcharenko, Roman; Paulus, Beate; Dedkov, Yuriy; Voloshina, Elena
Abstract: Electronic decoupling of graphene from metallic and semiconducting substrates via intercalation of different species is one of the widely used approaches in studies of graphene. In the present work, the modification of the electronic and magnetic properties of graphene on ferromagnetic Ni(111) layer via intercalation of halogen atoms (X = F, Cl, Br) is studied using the state‐of‐the‐art density‐functional theory approach. It is found that in all gr/X/Ni(111) intercalation systems, a graphene layer is fully electronically decoupled from the ferromagnetic substrate; however, different kind (electron or hole) and level of doping can be achieved. Despite the extremely small magnetic moment of C‐atoms in graphene observed after halogens intercalation, the sizeable spin‐splitting up to 35 meV for the linearly dispersing graphene π bands is found. The obtained theoretical data bring new ideas on the formation of the graphene‐ferromagnet interfaces where spin polarized free‐standing graphene layer can be formed with the possible application of these systems in electronics and spintronics. Abstract : Intercalation of halogens atoms can be used to decouple graphene from Ni(111) ferromagnetic substrate. Depending on the type and concentration of the intercalant, different levels of the electron‐ and hole‐doping can be achieved. In all cases, graphene‐derived π states around the K point and around the Fermi level remain spin‐polarised with a splitting reaching 35 meV.